THROMBOCYTOPENIA AND COVID-19: DIFFERENTIAL DIAGNOSIS AND THERAPY - Mitrovic, Mirjana; Pantić, Nikola M (Srpski medicinski časopis Lekarske komore, 2022)
Thrombocytopenia represents a common manifestation of COVID-19 with a prevalence of up to 35% in certain studies. A low platelet count is an unfavorable prognostic marker in SARS-CoV-2 infected patients. Despite a large number of publications dealing with the prognostic significance of thrombocytopenia in COVID-19, data regarding the differential diagnosis and therapy are scarce. The most common causes of thrombocytopenia in COVID-19 are shown in this review, namely: SARS-CoV-2-induced thrombocytopenia; disseminated intravascular coagulopathy (DIC); immune thrombocytopenia; drug-induced thrombocytopenia, with a special insight into heparin-induced thrombocytopenia (HIT). Although a majority of patients suffer from mild thrombocytopenia and do not require any particular treatment, there are some cases of severe thrombocytopenia which may cause life threatening bleeding. On the other hand, some forms of thrombocytopenia, such as DIC or HIT, carry a high risk of the development of thrombotic events, which is why anticoagulant prophylaxis is required in these patients. At the end of each section of this review, treatment recommendations are given for each aforementioned type of thrombocytopenia developing in COVID-19.